If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 21 = 7(x + 3) Reorder the terms: 21 + 6x = 7(x + 3) Reorder the terms: 21 + 6x = 7(3 + x) 21 + 6x = (3 * 7 + x * 7) 21 + 6x = (21 + 7x) Add '-21' to each side of the equation. 21 + -21 + 6x = 21 + -21 + 7x Combine like terms: 21 + -21 = 0 0 + 6x = 21 + -21 + 7x 6x = 21 + -21 + 7x Combine like terms: 21 + -21 = 0 6x = 0 + 7x 6x = 7x Solving 6x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6x + -7x = 7x + -7x Combine like terms: 6x + -7x = -1x -1x = 7x + -7x Combine like terms: 7x + -7x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 1-4k=-5k-1 | | -6-a=1+6a | | 5x-3=10x | | -5k+10k+16=1+2k | | -12x-14=-74 | | 5(8+7c)=390 | | 3x+15x+7=162 | | 7a-2=10+7a+4a | | 3/5x-2/3 | | 3/5x-2/5 | | -2+5v=9v+10 | | 12-9b=6-8b | | 2u+8u-5u= | | An=1/27*3^n-1 | | 1-8x=-7-6x | | 3/5x-2/5=3/10 | | -(3x-3)=-6-2x | | 17-9n=1-7n | | 4/3=v/8 | | 2x-5x=-5-2x | | 3r-6=2r-2r | | 0=3b+21 | | 1+3p=-4p+15 | | -18+7m=m-6-6 | | Y/3-3=11 | | 6n-14=4n+16 | | k-6=m+18 | | 3x=y+16 | | 3(-2x+1)=7(-3x-6) | | 7(5-2a)=5(-3a+1) | | 3x-5(x-4)=-2+3x-8 | | 8-5p+4P=5+2P-9 |